10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Japan will reach peak population aging around 2043. To better understand healthcare-seeking behaviors in depopulated and aging communities, we examined healthcare utilization patterns in rural areas of Japan throughout 2025. METHODS: Using the Ecology of Medical Care model, we conducted a descriptive study in a mountainous area of Japan. Health behaviors were summarized per 1000 population with 95% confidence intervals (CIs). RESULTS: A total of 1285 residents reported 2021 health problems. The median age was 63 years (interquartile range, 39-74 years), and 47.2% of respondents were aged ≥ 65 years. Per 1000 population (95% CI), the estimated numbers of individuals were: no symptoms, 782 (759-805); observation, 20 (13-28); self-care without medical consultation, 34 (24-43); clinic visits, 42 (31-53); primary hospital visits, 52 (40-64); secondary hospital visits, 31 (22-40); tertiary hospital visits, 8 (3-13); ambulance transport, 2 (0-5); hospitalization, 27 (18-36); and urgent home visits 2 (0-5). Self-care without medical consultation among young adults as well as hospitalizations and ambulance transports among those aged ≥ 75 years were more frequent; children often used higher-level hospital services. CONCLUSION: In rural mountainous communities, younger adults were more likely to rely on self-care, whereas older adults had higher rates of hospitalization, and children used centralized hospitals more frequently. These findings provide insight into healthcare-seeking patterns in communities experiencing population aging and decline.